Policy Formulation of The Rechterlijk Pardon Concept (Judge's Forgiveness) In Traffic Accident Criminal Cases - Nilvany Hardicky; Riadi Asra Rahmad; Heni Susanti (Journal of Law, Politic and Humanities, 2024)
The concept of Rechterlijk Pardon (Judge's Forgiveness) is a new concept that was born in the RKUHP, where Judges are given the authority to forgive perpetrators of criminal acts even if they are proven guilty. The aim of this research is to find out how the concept of Rechterlijk Pardon (Judge's Forgiveness) is used in criminal traffic accidents. The main problem in this research is how to apply the Rechterlijk Pardon (Judge's Forgiveness) concept in traffic accident criminal cases and what are the weaknesses of the Rechterlijk Pardon (Judge's Forgiveness) concept in the perspective of Indonesian criminal law. The research method used is normative juridical with techniques for searching legal materials by means of library studies, documentation studies and the internet. From the results of this research, it can be concluded that the concept of Rechterlijk Pardon (Judge's Forgiveness) can be applied to traffic accident cases if it meets the requirements based on the provisions of RKUHP Article 54 paragraph (2) "The severity of the act, the personal condition of the perpetrator, or the circumstances at the time the crime was committed and the what happens later can be used as a basis for consideration for not imposing a crime or not imposing humanitarian action." Not opposing the sense of justice for victims and not opposing the norms that exist in society. The concept of Rechterlijk Pardon (Judge's Forgiveness) is in line with the theory of Restorative Justice, which was used in the decision of the M. Rasyid Amrullah Rajasa case. The Rechterlijk Pardon (Judge's Forgiveness) concept has a weakness, namely that it can give rise to new problems, especially if the Rechterlijk Pardon (Judge's Forgiveness) concept is implemented in criminal case decisions, namely that there are no types of decisions that are not in accordance with the substance of this principle. It can be concluded that none of the types of decisions regulated in the Criminal Procedure Code are in accordance with the concept of Rechterlijk Pardon (Judge's Forgiveness).